2021
DOI: 10.3389/fmicb.2021.727937
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Microbiota in Proximal and Distal Colorectal Cancer and Their Relationships With Clinical Outcomes

Abstract: The proximal and distal subsites of colorectal cancer (CRC) have distinct differences in their embryonic origin, epidemiology, and prognosis. Therefore, they are not considered as the same disease. However, the possible difference in microbial characterization of the two subsites of CRC is still unclear. In this study, we explored tumor microbiota diversity and composition difference in patients with proximal (N = 187) and distal CRCs (N = 142). This was carried out on cancer tissues and adjacent tissues using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
2
16
1
Order By: Relevance
“…This is also consistent with the evidence of the gut microbiota acting in the early stages of colon carcinogenesis [23], emphasizing the potential benefit of fermented food against cancer development, especially in those sites of the colon where bacteria mostly exert their function [24]. Indeed, different compositions of gut microbiota have been described in relation to different CRC types and outcomes [25,26]. Our data refer to the year before CRC diagnosis/interview, used as a proxy for usual diet of the participants who could have changed their habits once aware of the disease or because of symptoms [27].…”
Section: Discussionsupporting
confidence: 87%
“…This is also consistent with the evidence of the gut microbiota acting in the early stages of colon carcinogenesis [23], emphasizing the potential benefit of fermented food against cancer development, especially in those sites of the colon where bacteria mostly exert their function [24]. Indeed, different compositions of gut microbiota have been described in relation to different CRC types and outcomes [25,26]. Our data refer to the year before CRC diagnosis/interview, used as a proxy for usual diet of the participants who could have changed their habits once aware of the disease or because of symptoms [27].…”
Section: Discussionsupporting
confidence: 87%
“…One study analyzed the microbial diversity in the tumor tissues from different intestinal locations and found that the proximal intestinal cancer tissues are significantly richer in intestinal bacteria than the distal intestinal cancer tissues. 39 In 2012, Tjalsma H et al were the first to propose a “driver‐passenger” model to explain the “adenoma‐carcinoma” progression of CRC. 40 The model suggests that driver bacteria promote the colonization of passenger bacteria by altering the intestinal microenvironment, and differences in the types of driver and passenger bacteria are found at different stages of CRC development.…”
Section: Intestinal Mucosal Tissue Microbiome and Early Detection Of Crcmentioning
confidence: 99%
“…Moreover, the heterogeneity of the tissue microbiome in different CRC stages indirectly suggests that the fecal microbiome and blood microbiome of CRC stage heterogeneity. One study analyzed the microbial diversity in the tumor tissues from different intestinal locations and found that the proximal intestinal cancer tissues are significantly richer in intestinal bacteria than the distal intestinal cancer tissues 39 . In 2012, Tjalsma H et al were the first to propose a “driver‐passenger” model to explain the “adenoma‐carcinoma” progression of CRC 40 .…”
Section: Intestinal Mucosal Tissue Microbiome and Early Detection Of Crcmentioning
confidence: 99%
“…association probability ŷ of original prediction and association probability ŷs of post intervention prediction. Our purpose is that the model can make the best choice between ŷ and ŷs for the final prediction, so as to reduce the impact caused by the local structural difference of nodes [25], which is calculated as follows:…”
Section: Select Algorithmmentioning
confidence: 99%